Share
Explore BrainMass

Principal Value Proof

Prove that if all of the powers invoved are principal values then...

Please see the attached file for the fully formatted problems.

Attachments

Solution Preview

a)
We can write:

z=r*exp(i*theta)

1/z=1/r*exp(-i*theta) --->

(1/z)^c= (1/r)^(c)*exp(-i*c*theta))= r^(-c)*exp(-i*c*theta)= [r*exp(i*theta)]^(-c)= z^(-c)

Note that we are considering the principal value, so we do not have to worry about c.

b)

z=r*exp(i*theta)

z^c= ...

Solution Summary

A Principal Value Proof is provided.

$2.19